Political violence in the G5 Sahel countries -- Conflict diffusion indicator: Methodology and implementation - Hema, Aboubacar; Marivoet, Wim (Github, Inc., 2025)
The Conflict Diffusion Indicator, as defined by ACLED, measures the proportion of a country’s geographic area experiencing high levels of violence. This indicator assesses the geographic spread of conflict across administrative level 2 (adm2) regions, using a 10km-by-10km spatial grid. This document outlines the methodology and implementation steps for computing the indicator for the Sahel region (2018 data) using Google Earth Engine (GEE).